Food Insecurity among Low-Income Households with Children Participating in a School-Based Fruit and Vegetable Co-Op - Allison N. Marshall; Ru-Jye Chuang; Joanne Chow; Nalini Ranjit; Jayna M. Dave; Mallika Mathur; Christine Markham; Shreela V. Sharma (MDPI AG, 2022)
The purpose of this study was to evaluate the impact of a nutrition intervention on food insecurity among low-income households with children. Data were collected from 371 parent-child dyads in a quasi-experimental evaluation study of a 1-year intervention (n = 6 intervention schools receiving Brighter Bites, n = 6 wait-list control schools), and longitudinal follow-up of the intervention group 2 years post-intervention in Houston, Texas. Data were collected at three timepoints: at baseline and 1 year for all participants, and at 2 year follow-up for the intervention group (the wait-list control group received the intervention during that time). At baseline, most parents reported food insecurity (60.6%; 70% intervention group, 53.6% control). Food insecurity decreased significantly from 81.3% to 61.7% [(−0.32, −0.07) p = 0.002] among intervention participants immediately post-intervention. After adjusting for ethnicity, 2 years post-intervention the predicted percentage of participants reporting food insecurity decreased significantly by roughly 35.4% from 76.4% at baseline to 41.0% [(−0.49, −0.22), p < 0.001]. Between-group changes were not significant. The re-sults of this study demonstrated a significant positive impact of Brighter Bites on food security in the short and long-term among low-income households with children, albeit results should be in-terpreted with caution.